Lecture Notes on Quantum Mechanics - Samuel, D Lindenbaum (World Scientific, 1999)
This book is written based on lecture notes covering three to four semesters of graduate courses in quantum mechanics. The author sets out by explaining the physical concepts of quantum mechanics, and then goes on to describe the mathematical formalism and present illustrative examples of the ideas and methods that serve to amplify points discussed in the text. Exercises, with solutions, are included.The chapters are not independent, but build on one another. Subjects range from the failures of classical theory to second quantization, including chapters on the Dirac theory and Feynman diagrams. The book is intended for use as a graduate level text as well as a reference. Cuốn sách này được viết dựa trên các ghi chú bài giảng bao gồm ba đến bốn học kỳ của các khóa học sau đại học về cơ học lượng tử. Tác giả đặt ra bằng cách giải thích các khái niệm vật lý của cơ học lượng tử, và sau đó tiếp tục mô tả chủ nghĩa hình thức toán học và trình bày các ví dụ minh họa về các ý tưởng và phương pháp phục vụ cho việc khuếch đại các điểm được thảo luận trong văn bản. Các bài tập, với lời giải, được bao gồm trong các chương không độc lập mà được xây dựng dựa trên nhau. Các chủ đề trải dài từ những thất bại của lý thuyết cổ điển đến lượng tử hóa thứ hai, bao gồm các chương về lý thuyết Dirac và biểu đồ Feynman. Cuốn sách được sử dụng như một văn bản cấp độ sau đại học cũng như một tài liệu tham khảo.